PENYULUHAN DAN PELATIHAN : INOVASI PEMBUATAN SABUN RAMAH LINGKUNGAN DARI BUAH KLERAK (Sapindus rarak DC.) - Andari, Susilowati; Ita Octafia; Cinthya Ratna Yuniar; Listiyana Sintiya Putri; Ulfi Uswatun Khasanah; Vannesa Herlinnasti; Vina Nurul Khamidiyah; Wafirotul Elifah; Wahyu Rizky Pratama (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The use of synthetic chemical-based detergents often leads to environmental pollution problems. The results of the study by Muhamed et al. (2018) indicate that laundry wastewater (greywater) containing detergents alters soil characteristics, such as an increase in pH and electrical conductivity, and a decrease in the rate of infiltration. Based on the literature review conducted by Naufal and A’yun (2024), carelessly discarded detergent waste contains active substances like phosphate, surfactant, and bleach, which can reduce soil quality, disrupt microorganisms, and impact public health. The lerak fruit (Sapindus rarak) is a natural material with a high saponin content that can therefore be utilized as a raw material for eco-friendly soap. This community service program aims to provide knowledge and popularize the use of lerak fruit as a raw material for eco-friendly soap. The activity was carried out in collaboration with PKK members in Sambilawang Village, Bungkal, Ponorogo. The methods used included counseling/extension using PowerPoint media and brochures, as well as the practice of making lerak soap. To measure the effectiveness of the activity, pre-tests and post-tests were conducted before and after the activity. This activity is a tangible contribution to making the PKK members self-reliant and empowering them to utilize local natural resources. It is hoped that this extension program can become a solution to the pollution problems resulting from detergent use and increase community productivity. Based on the N-Gain score analysis, which showed a figure of 84%, the method used was effective in increasing the participants' knowledge.